Céline: The Authorized Biography - Germain, Georges-Hébert (Dundurn Press, 1998)
Simply entitled Céline, this is the long-awaited, authorized biography of Céline Dion, the rags-to-riches story of a woman who has become the leading recording artist in the world. First published in French in Quebec in December 1997, Céline has sold in excess of 120,000 copies in Quebec alone. A French-language edition will be released in France this fall, to coincide with the release of a new French album.

Sacred songs and arias by women composers: A survey of the literature and performer's analysis of selected works by Isabella Leonarda, Luise Reichardt, Ethel Smyth, Violet Archer, Margaret Bonds and Edith Borroff - Heape, Mary Willis (Séminaire théologique baptiste du Sud-Ouest, 1995)
This document is written in support of a recital of sacred songs and arias by women composers. It is divided into two sections: a survey of sacred music, specifically sacred arts songs and sacred arias from larger works, and a performer's analysis of selected works drawn from the research of the first part. The survey begins with the commercial printing of music around 1500 and extends to 1994. Countries from around the world are represented, some more broadly than others. Biographical information, when available, is given for each composer featured in the survey as well as some discussion of her general compositional style and output. Greater attention is given to the composer's sacred music, especially compositions that involve the solo voice. Composers who wrote very little sacred music for the solo voice are mentioned only briefly. The performer's analysis includes biographical information on each composer as well as a discussion of her general style, significant compositions, honors and awards and sphere of influence. In the analysis of the pieces, attention is focused on elements in the music that affect its performance. The selected works include Volo Jesum, a solo motet by Isabella Leonarda, "An Maria," "Stille der Andacht" and "Die Blume der Blumen," three art songs by Luise Reichardt, "Benedictus" from Mass in D by Ethel Smyth, Violet Archer's Three Biblical Songs, Five Spirituals by Margaret Bonds and Missa Patrinae Rerum Domini, a setting of the mass for solo voice by Edith Borroff. The appendices include work lists of the selected composers, IPA transcriptions of the pieces, a chronological listing of composers, and a copy of the program, program notes and lecture from the recital. An extensive bibliography is included.
Keywords: Archer; Bonds; Borroff; Communication and the arts; Edith; England; Ethel; Germany; Isabella; Leonarda; Luise; Margaret; Reichardt; Smyth; Social sciences; Violet

Sacred Song Sisters: Choral and Solo Vocal Church Music by Women Composers for the Lenten Revised Common Lectionary - Elliott, Lisa A. (Université du Nevada, 2020)
This document explores sacred music by women composers for the Revised Common Lectionary (RCL) of the Catholic and Christian churches. The study researches exclusively choral and vocal solo music by women composers for the church season of Lent. Other primary limitations include music in English, and music from the nineteenth century to the present. The main question answered in this document is: what sacred music has been published by women composers that may be programmed in church services? This question is answered in the included appendices. These appendices list the music by women composers appropriate for the specific RCL readings for each Sunday of Lent, as well as the holidays of Ash Wednesday, Maundy Thursday, and Good Friday. There are also appendices of choral and solo vocal pieces that are generally appropriate for the Lenten season. Every attempt was made to be as thorough as possible in identifying this music, with the understanding that no one compilation of this kind can ever be complete. Additionally, selected works by six composers are explored in this document: Emma Lou Diemer (b. 1927), Arletta O’Hearn (b. ca 1928), Jane M. Marshall (1924 – 2019), Rebecca Clarke (1886 – 1979), Violet Archer (1913 – 2000), and Undine Smith Moore (1904 – 1989). These composers are representative of the variety of styles, diversity, history, and levels of musical complexity within this body of music.
Keywords: Choir; Christ; Female; Service; Sing; Worship

The Songs of Violet Archer: Tracing the Evolution of One of Canada's Most Prominent Composers - Dauphinais, Paul (Université de Boston, 2016)
In this study, four sets of songs composed by Violet Archer are examined, all of which were written at different points in her career. Archer studied with Paul Hindemith in 1948 – 49, and his teachings had a tremendous impact on the young composer. The first set of songs to be analyzed, Moon Songs, was written before her time with Hindemith, and will provide a baseline from which her later, post-Hindemith, works can be compared. Following her studies with Hindemith, Archer wrote three songs, “Cradle Song,” “April Weather,” and “First Snow,” all of which show evidence of Hindemith’s influence. Her later, more mature works, Northern Landscape and Caleidoscopio Quatro, demonstrate a refined compositional technique; one in which Archer has created her own style, while maintaining aspects of the approach taught by Hindemith at Yale. This study will elaborate on the aspects of Archer’s music that evolved throughout her compositional career.
Keywords: Archer; Communication and the arts; Hindemith; Music analysis; Paul; Social sciences; Violet

Violet Archer's "The Twenty-Third Psalm" (1952): An Analytical Study of Text and Music Relations Through Fibonacci Numbers, Melodic Contour, Motives, and Piano Accompaniment - Wan, Jessica Jane (Université d'Ottawa, 2012)
This study explores text and music relations in Canadian composer Violet Archer's “The Twenty-Third Psalm” by analysing the text of Psalm 23, Fibonacci numbers, melodic contours, motives, and the role of the accompaniment. The text focuses on David's faith in God and his acceptance of God as his shepherd on earth. The four other approaches allow us to examine the work on three different structural levels: background through Fibonacci numbers, middleground through melodic contour analysis, and foreground through motivic analysis and the role of the accompaniment. The measure numbers that align with Fibonacci numbers overlap with some of the melodic contour phrases, which are demarcated by rests, as well as with the most important moments at the surface level, such as the emphasis on the word “death” through recurring and symbolic motives. The piano accompaniment further supports these moments in the text.
Keywords: Archer; Canadian music; Communication and the arts; Fibonacci numbers; Melodic contour; Motivic analysis; Music analysis; Psalm 23; Text and music relations; The Twenty-Third Psalm (1952); Theory; Violet